Implementasi Perbankan Islam: Pengaruh Sosio-Eko¬nomis Dan Peranannya Dalam Pembangunan - Achmad Tohirin (Universitas Islam Indonesia, 2003)
The major distinctive feature of the Islamic banking as compared to the conventional one lies on the pricing mechanism. The ‘new’ system applies variable pricing mechanism, as reflected on the Profit and Loss Sharing (PLS) system, meanwhile the ‘old’ system applies fixed pricing mechanism, as reflected on the Interest Based (IB) system. Several implications arise from this very basic difference. This paper discusses the implementation of Islamic banking, its socio-economic effect and its role in the development. As a new type of banking system, Islamic banking attracts serious attention from the business players and regulatory authority as well, around the world. The discussion in this paper includes comparison be¬tween these two systems on several instances; the socio-economic effect of the implementa¬tion of Islamic banking; and its role on the (economic) development. In addition the paper also prescribes the direction and the policy required for developing Islamic bank.Keywords: Islamic banking, Profit and Loss Sharing, community welfare